Sport and foreign policy in Cuba in the 1970s and 1980s - Valentin, Renato Beschizza [UNESP] (Univ Passo Fundo, 2024)
The present article contains an analysis of the role played by sport in Cuban foreign policy during the 1970s and 1980s. The historical reconstruction of the nexuses between sport and foreign policy in Cuba was formulated on the basis of the results of an investigation and analysis of previously secret documents of the United States government. During the historical period of this article, the Cuban sports exchange included the sending and receiving sports teams and delegations, the training of foreign sports specialists within Cuba, the increasing presence of coaches from socialist countries working in Cuban sport, the sending of Cuban coaches abroad, and the construction of sports infrastructure in other Third World countries.
Keywords: Sport; Foreign policy; Cuban revolution